2009
DOI: 10.1089/jir.2008.0099
|View full text |Cite
|
Sign up to set email alerts
|

GAGE, an Antiapoptotic Protein Binds and Modulates the Expression of Nucleophosmin/B23 and Interferon Regulatory Factor 1

Abstract: The GAGE family of highly related tumor antigens is expressed in a variety of tumors. This albeit silent gene expression resulted in resistance of cells to various apoptotic agents such as Fas, interferon-gamma, Taxol, or gamma-radiation. We now report that GAGE overexpression in either HeLa (expressing endogenous GAGE) or HEK293 (devoid of GAGE expression) rendered those cells unsusceptible to cell death induced by IFN-gamma. We investigated the underlying mechanism of GAGE-induced cell survival upon treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…GAGE also binds and increases the abundance of tumor suppressor NPM/B23. 9 Kondo et al has shown that NPM/B23 and IRF-1 exist as a complex and we have shown that GAGE could also be a part of the complex. 9,10 The above studies were performed with full length GAGE protein and we are interested in finding the region of GAGE that is responsible for its effect.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…GAGE also binds and increases the abundance of tumor suppressor NPM/B23. 9 Kondo et al has shown that NPM/B23 and IRF-1 exist as a complex and we have shown that GAGE could also be a part of the complex. 9,10 The above studies were performed with full length GAGE protein and we are interested in finding the region of GAGE that is responsible for its effect.…”
Section: Introductionsupporting
confidence: 57%
“…9 Kondo et al has shown that NPM/B23 and IRF-1 exist as a complex and we have shown that GAGE could also be a part of the complex. 9,10 The above studies were performed with full length GAGE protein and we are interested in finding the region of GAGE that is responsible for its effect. Small size of GAGE protein (117 amino acids) prompted us to design five peptides that could encompass whole sequence of GAGE protein.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…An unexpected family of tumor antigens, GAGE, was induced during RSV infection. These antiapoptotic tumor antigens are capable of interacting with IRF1 and of reducing its expression (27), which may help explain the weak interferon response observed in RSV-infected hAECs at both the transcriptional and protein levels. Our observations highlight the plasticity of the airway epithelium to elicit virus-specific immune effector responses.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have suggested that CT antigens during carcinogenesis may play an important role in maintaining cell survival (i.e., inhibition of apoptosis), [17][18][19] promoting resistance to various forms of chemo-and radio-therapy 20,21 and contributing to oncogenesis by targeting p53 and p21 tumor suppressor genes. 22,23 Also, since SYCP1 (Synaptonemal Complex Protein 1), SYCP3, DMC1 (Disrupted Meiotic cDNA 1), and REC8 CT antigens under normal conditions regulate generation of double strand DNA breaks during crossing over in meiosis, it was suggested that these genes may promote aneuploidy and genomic instability in cancers by producing aberrant chromosomal translocations.…”
mentioning
confidence: 99%